A Retrospective Study of DNA Analysis Thalassemia Patients in Jambi Province for the Years 2016-2020 - Hutabarat, Sabar; Aurora, Wahyu Indah Dewi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
ABSTRACT Background: Thalassemia is a genetic blood disorder characterized by abnormal hemoglobin production, leading to anemia. Beta-thalassemia, particularly its transfusion-dependent form, requires lifelong care. DNA analysis plays a crucial role in diagnosing thalassemia, providing precise methods for genetic counseling, prenatal diagnosis, and effective prevention programs. This research aims to describe the results of DNA analysis of thalassemia patients in Jambi Province from 2016 to 2020. Methods: This study uses a descriptive retrospective design. Data were analyzed from the medical records of thalassemia patients identified in Jambi Province between 2016 and 2020. The research subjects are individuals diagnosed with thalassemia within this period, with data collection performed via total sampling, encompassing 25 respondents. Results: The majority of thalassemia patients in Jambi Province are children aged 5-14, with a significant proportion having a history of blood transfusions for more than a year. Most patients are classified as Beta Thalassemia (96%), consistent with global trends. DNA analysis revealed significant variation in mutations, with common mutations such as Hb E and IVS-nt-5 found in 48% of samples. The study highlights the genetic diversity within the thalassemia patient population, indicating variations in disease severity. Conclusion: This study highlights the importance of early detection and management of thalassemia, particularly in children. Blood transfusions are crucial for maintaining the health of thalassemia patients in Jambi Province, where Beta Thalassemia is most common. DNA analysis reveals significant genetic diversity, which helps in selecting appropriate treatments and understanding the risk of complications. These findings provide a basis for improving diagnostic and management strategies for thalassemia in Jambi Province.